Implementation of the Advanced Encryption Standard (AES) Algorithm and Bit Plane Complexity Segmentation (BPCS) Steganography Technique for Enhancing Text File Security - Kautsar, Afthar; Ikhsan, Muhammad (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
In today's digital era, data security has become a crucial aspect due to the vast amount of information being transmitted and stored electronically. The Advanced Encryption Standard (AES) is one of the most widely used encryption algorithms because of its high level of security. However, data that is merely encrypted still risks detection; therefore, the Bit-Plane Complexity Segmentation (BPCS) steganography technique is employed to hide data within digital images, making it more difficult to identify. This study aims to enhance data security by combining AES encryption and BPCS steganography. The process begins by encrypting text data using AES-128, ensuring that the information cannot be accessed without a valid key. Next, the resulting ciphertext is embedded into a digital image using the BPCS technique, which selects bit-planes with high complexity for insertion without significantly altering the visual appearance of the image. Testing is conducted by measuring the accuracy of data extraction and the impact on image quality. The results indicate that this method effectively maintains data security and confidentiality. The data embedded in the image can be extracted with a success rate of 100%, while the image quality remains intact without noticeable changes. Thus, the combination of AES and BPCS provides a dual layer of protection: encryption ensures that the data cannot be read, while steganography conceals the existence of the data from unauthorized parties. This method can be applied in various data security scenarios, both for personal and organizational purposes.